Quantitative Assessment of the Effects of Oxidants on Antigen-Antibody Binding In Vitro. (24th May 2016) - Han, Shuang; Wang, Guanyu; Xu, Naijin; Liu, Hui
Abstract : Objective. We quantitatively assessed the influence of oxidants on antigen-antibody-binding activity. Methods. We used several immunological detection methods, including precipitation reactions, agglutination reactions, and enzyme immunoassays, to determine antibody activity. The oxidation-reduction potential was measured in order to determine total serum antioxidant capacity. Results. Certain concentrations of oxidants resulted in significant inhibition of antibody activity but had little influence on total serum antioxidant capacity. Conclusions. Oxidants had a significant influence on interactions between antigen and antibody, but minimal effect on the peptide of the antibody molecule.